Mixed donor, phenanthroline photoactive MOFs with favourable CO2 selectivity. Issue 87 (9th October 2020) - Setter, Caitlin J.; Price, Michael B.; Conte, Luke; Schmitt, Wolfgang; Batten, Stuart R.; Richardson, Christopher; Hill, Matthew R.; Babarao, Ravichandar; Macreadie, Lauren K.
Abstract : Mixed donor phenanthroline-carboxylate linkers were combined with Mn II or Zn II to form photoactive MOFs with large pore apertures. Abstract : Mixed donor phenanthroline-carboxylate linkers were combined with Mn II or Zn II to form photoactive MOFs with large pore apertures. The MOFs display high CO2 adsorption capacities, which consequently causes structural framework flexibility, and align with favorable metrics for selective CO2 capture. The photophysical properties of the MOFs were investigated, with the Mn II MOF giving rise to short triplet LMCT lifetimes.